Analysis and Construction of the Relationship between Teachers and Students in Colleges and Universities - Bai, Jingpan; Zhu, Silei; Chen, Yuan; Ji, Houling; Bai, Kai (Journal of Research in Vocational Education, 2025)
The teacher-student relationship in colleges and universities is a key and significant relationship in higher education as a whole. It is the guarantee for the smooth progress of educational and teaching activities, the foundation for building a harmonious campus, the premise for the effective implementation of education, and the catalyst for achieving mutual learning between teachers and students. However, there are still some problems in the current teacher-student relationship in colleges and universities that need to be further improved. This article analyzes the problems in the teacher-student relationship based on the types of bad teachers and students and the adverse effects caused. Furthermore, it analyzes the required teacher-student relationship and puts forward suggestions for its construction. It is hoped that the suggestions put forward can further improve and promote the healthy development of the teacher-student relationship in colleges and universities.